2022
DOI: 10.3390/land11081178
|View full text |Cite
|
Sign up to set email alerts
|

Flood Hazard Index Application in Arid Catchments: Case of the Taguenit Wadi Watershed, Lakhssas, Morocco

Abstract: During the last decade, climate change has generated extreme rainfall events triggering flash floods in short periods worldwide. The delimitation of flood zones by detailed mapping generally makes it possible to avoid human and economic losses, especially in regions at high risk of flooding. The Taguenit basin, located in southern Morocco, is a particular case. The mapping of the flood zones of this basin by the method of the Flood Hazard Index (FHI) in a GIS geographic information systems environment was base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 54 publications
0
37
0
Order By: Relevance
“…The area has two distinct types of savanna vegetation of Sudan Savanna and Sahel Savanna. The major economic activity in the basin is agriculture [49], with about 80% of its surface area being arable land, supporting about 85% of the total population [34,41].…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…The area has two distinct types of savanna vegetation of Sudan Savanna and Sahel Savanna. The major economic activity in the basin is agriculture [49], with about 80% of its surface area being arable land, supporting about 85% of the total population [34,41].…”
Section: Study Areamentioning
confidence: 99%
“…A Geographic Information System (GIS) is an important tool for mapping flood risk [25][26][27][28][29][30][31][32][33][34]. Behazin et al [18] and Ikirri et al [34] argued that the integration of remote sensing and GIS techniques coupled with the Analytical Hierarchical Process (AHP) are the best techniques for flood risk and vulnerability assessment, especially in areas with sparse or outdated data. This technique was adopted here for flood risk mapping and vulnerability assessment in the Hadejia River watershed due to limited data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, flow accumulation in Jakarta tends to be homogeneous due to the flat topography of the area (Ng et al, 2012). The higher of accumulation flow in an area will be directly proportional to the potential for the area to experience flooding (Ikirri et al, 2022;Mahmoud and Gan, 2018). On the other hand, areas with low accumulated flow rates have less potential to experience flooding.…”
Section: Spatial Analysis Of the Causes Of Flooding In Jakartamentioning
confidence: 99%
“…Considering the application of FFPI for Kyushu Island, Japan, the researchers found that a few hydrograph characteristics, such as the time to peak or peak discharge, were considered in the study. In Morocco, the flash hazard index (FHI) was used to generate the flood susceptibility mapping using rainfall, slope, flow accumulation, drainage network density, distance from rivers, permeability, and land use [11]. In the flash flood guidance provided by the US National Weather Service, the peak time of the hydrograph is a parameter that should be considered in the system [12].…”
Section: Introductionmentioning
confidence: 99%